Historical Neighborhood Poverty Trajectories and Child Sleep - Sheehan, Connor (Sleep Health, 2018)
OBJECTIVES: To determine whether historical neighborhood poverty measures are associated with mothers’ reports of their children’s sleep duration and to compare results from historical neighborhood poverty measures to contemporaneous measures of neighborhood poverty. DESIGN: The Geographic Research on Wellbeing (GROW) study is a follow-up survey of mothers who gave birth between 2003-2007. GROW mothers assessed their own and their children’s health and health behaviors 5-10 years later (2012-2013). SETTING: Urban Californian counties. PARTICIPANTS: GROW respondents. MEASUREMENTS: We categorized children’s sleep as adequate or inadequate using clinical age-specific guidelines and based on mothers’ reports of their child’s sleep duration. We conducted a latent class analysis to identify historical poverty classes for all California census tracts using data from 1970 to 2005-2009, and we categorized current neighborhood poverty based on data from 2005-2009 only. We then assigned children to different neighborhood exposure classes based on their neighborhood of residence at birth and follow-up. RESULTS: Logistic models indicated that net of controls for demographics, child behavior and health characteristics, mother characteristics, and household socioeconomic status, children who grew up in historically low (OR: 0.64, 95% CI = 0.45-0.92) or historically moderate poverty classes (OR: 0.68, 95% CI = 0.48-0.98) had lower odds of inadequate sleep duration compared with children who grew up in historically high poverty. We show that the historical specification of neighborhood poverty remained significant despite controls while contemporaneous measures of neighborhood poverty did not. CONCLUSIONS: Our findings indicate strong associations between historical neighborhood poverty and child sleep duration.